Individual vs. Group Cognitive Behavior Therapy for Anxiety Disorder in Children and Adolescents: A Meta-Analysis of Randomized Controlled Trials - Guo, Tingting; Su, Jing; Hu, Jiayi; Aalberg, Marianne; Zhu, Yinglin; Teng, Teng; Zhou, Xinyu (Frontiers in Psychiatry, 2021)
Background: Anxiety disorder is the most prevalent mental disorder in children and adolescents. However, evidence for efficacy and acceptability between individual cognitive behavior therapy (I-CBT) and group cognitive behavior therapy (G-CBT) in anxiety disorders in children and adolescents remains unclear. Methods: Eight electronic databases (PubMed, Embase, Cochrane, Web of Science, CINAHL, PsycINFO, ProQuest, and LILACS) were searched from inception to October 2019. Randomized controlled trials comparing I-CBT with G-CBT for anxiety disorders in children and adolescents were included. The primary outcomes were efficacy (mean change in anxiety symptom scores) at post-treatment and acceptability (all-cause discontinuation). The secondary outcome was remission at post-treatment. Subgroup analyses were also conducted to examine whether the result would be influenced by age, number of treatment sessions, parental involvement, male/female sex, and number of participants. Results: Nine studies were selected in this meta-analysis. The pooled analyses indicated no significant difference between I-CBT and G-CBT for efficacy at post-treatment [standardized mean difference (SMD), −0.14; 95% confidence interval (CI), −0.37 to 0.09], acceptability [odds ratio (OR), 1.30; 95% CI, 0.61–2.77], and remission at post-treatment (OR, 1.15; 95% CI, 0.79–1.66). In the subgroup analysis of age, I-CBT was significantly more effective than G-CBT in adolescents at post-treatment (SMD, −0.77; 95% CI, −1.51 to −0.02), but not in children (SMD, 0.00; 95% CI, −0.02 to 0.20). However, the findings were not materially different from those of the efficacy subgroup analysis of number of treatment sessions, parental involvement, male/female sex, and number of participants. Conclusions: Based on those current evidence, I-CBT was shown to be more beneficial than G-CBT for anxiety disorders in adolescents, but not in children. However, further well-designed clinical studies should be performed to confirm these findings. Systematic Review Registration:http://osf.io/xrjkp, identifier: 10.17605/OSF.IO/XRJKP.